EMPLOYEE PERFORMANCE PT. MILLENIUM PHARMACON INTERNATIONAL Tbk: QUALITY OF HUMAN RESOURCES (HR) AND INFORMATION SYSTEMS OF MILLENIUM PHARMACON INTERNATIONAL (SIMPI) - Eka Lufitasari; Mochamad Mochklas; Djoko Soelistya (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Companies must be able to compete, so it requires quality human resources (HR) and technology in the form of applications implemented by the company that can assist in achieving the company's vision and mission. This research aims to analyze the influence of the quality of human resources and the Millennium Pharmacon International (SIMPI) Information System Application on the Performance of PT. Millenium Pharmacon International Tbk. This study uses a quantitative approach, where the population and research sample of all employees of PT. Millenium Pharmacon International Tbk. Surabaya branch as many as 85 people. The incoming data is processed and analyzed using the SPSS-26 program. The results of this study the quality of human resources has a positive but insignificant effect on the performance of employees of PT. Millenium Pharmacon International Tbk, SIMPI has a positive and significant effect on the employee performance of PT. Millenium Pharmacon International Tbk, and the quality of HR and SIMPI simultaneously have a positive and significant effect on the performance of employees of PT. Millenium Pharmacon International Tbk.